A boronic acid–modified C60 derivatization reagent for the rapid detection of 3‐monochloropropane‐1, 2‐diol using matrix‐assisted laser desorption/ionization‐mass spectrometry. (11th August 2021) - Qin, Zhang‐Na; Ding, Jun; Yu, Qiong‐Wei; Zhou, Ping; Feng, Yu‐Qi
Abstract : Rationale: 3‐Monochloropropane‐1, 2‐diol (3‐MCPD) is a well‐known contaminant formed in food thermal processing, which could be found in a variety of foodstuffs. Due to its potential carcinogenicity, it was essential to quickly develop a rapid and high‐throughput analytical method to monitor 3‐MCPD in foodstuffs, which is described in this study. Methods: 3‐MCPD was extracted from foodstuffs and then was derivatized with a boronic acid–modified C60 (B‐C60 ) through the boronic acid‐diol reaction. Microwave heating was used to accelerate the derivatization reaction. Mass spectrometry (MS) analysis was conducted using matrix‐assisted laser desorption/ionization‐MS (MALDI‐MS). The application of the method was validated using various smoked food samples. Results: The chemical derivatization of 3‐MCPD with B‐C60 enabled the addition of a C60 ‐tag to 3‐MCPD. High‐throughput analysis of the sample within 0.5 h was realized. A good linear range from 0.02 to 1.5 μg mL −1 for 3‐MCPD was obtained, with a detection limit of 0.005 μg mL −1 . The recoveries in spiked foodstuffs ranged from 85.4% to 115.1% with relative standard deviations of 2.0%–14.2%. This method was successfully applied to detect 3‐MCPD in smoked foodstuffs. Conclusions: A quantitative method was developed for the detection of 3‐MCPD in foodstuffs using B‐C60 derivatization combined with MALDI‐MS strategy. This proposed method may serve as a potential platform for the rapid and high‐throughput analysis of 3‐MCPD in foodstuffs for the purpose of food safety control.